Tibet's great yogī, Milarepa - W. Y. Evans-Wentz (Oxford University Press, 2000)
This life story of Milarepa--the important Tibetan religious leader who lived over 800 years ago--is part of a remarkable four-volume series on Tibetan Buddhism produced by the late W.Y. Evans-Wentz, all four of which are being published by Oxford in new editions. While there are many parochial differences among the several sects of Tibetan Buddhism, each holds the Great Yogi Milarepa in the highest reverence and esteem. For exemplified in Milarepa's life, as we discover in these pages, are all of the teachings of the great yogis of India--including those of Gautama the Buddha, the greatest yogi known to history.